PENGARUH TERPAAN VIDEO TIKTOK @CERITAMODISFASHION DALAM MENINGKATKAN BRAND AWARENESS MODIS FASHION STORE PADA REMAJA KOTA DENPASAR - Melania, Bulan; Suryawati, I Gusti Agung Alit; Joni, I Dewa Ayu Sugiarica; Damasemil, Calvin (E-Jurnal Medium; Vol 4 No 1 (2023): Jurnal Ilmu Komunikasi Vol 4 No 1 Tahun 2023, 2023)
One of the women's clothing outlets that uses the TikTok application as a marketing medium is Modis Fashion Store, as evidenced by the TikTok account @Ceritamodisfashion which now has 2.1 million followers on the TikTok application. This study aims to determine the effect of Tik Tok @Ceritamodisfashion content in increasing Modis Fashion Store Brand Awareness among teenagers in the city of Denpasar. The results found in this study are 76.7% of the Fashion Store's Fashion Store Brand Awareness in teenagers in Denpasar, which is influenced by exposure to the video content of TikTok @Ceritamodisfashion. The remaining 23.3% is influenced by other variables outside of this study. However it has positive and significant . Keywords: Brand Awareness, Modis Fashion Store